Myodes rutilus ... - Jo, Yeong-Seok; Baccus, John T.; Koprowski, John L. (Zenodo, 2018)
Myodes rutilus (Pallas, 1778) —Northern Red-backed Vole Mus rutilus Pallas, 1778 p.246; Type locality- Center of Ob River delta, Siberia, Russia. Arvicola (Hypudaeus) amurensis Schrenck, 1858 p.129; Type locality- Mouth of Amur River, Siberia. Clethrionomys rutilus hintoni Vinogradov in Zolotarev, 1936 p.81; Type locality- Iman River, Ussuri, southeastern Siberia; Jones & Johnson, 1965 p.375. C. amurensis amurensis: Kuroda, 1938 p.5. C. rutilus: Won, 1968 p.207; Corbet, 1978 p.98; Han, 1994 p.47; Won & Smith, 1999 p.25; Han, 2004c p.134. C. rutilus amurensis: Won, 1968 p.208; Yoon, 1992 p.74. Myodes rutilus: Musser & Carleton, 2005 p.1027. Range: Myodes rutilus occurs in the extreme northeastern region of the Korean Peninsula (Fig. 121). The southern limit of the range is in Chail Peak, Ryanggang-Province (Kim et al. 2015). Remarks: The northern red-backed vole in Korea has been regarded as M. r. hintoni or M. r. amurensis. Although hintoni is now considered a synonym of amurensis (Won 1968), a ... : Published as part of Jo, Yeong-Seok, Baccus, John T. & Koprowski, John L., 2018, Mammals of Korea: a review of their taxonomy, distribution and conservation status, pp. 1-216 in Zootaxa 4522 (1) on page 178, DOI: 10.11646/zootaxa.4522.1.1, http://zenodo.org/record/2610198 ...